Patients with Small Abdominal Aortic Aneurysm are at Significant Risk of Cardiovascular Events and this Risk is not Addressed Sufficiently. (February 2017) - ,; Pathak, R.; Brooks, M.; Hayes, P.; Imray, C.; Quarmby, J.; Choksy, S.; Earnshaw, J.; Shearman, C.P.; Grocott, E.; Rix, T.; Chetter, I.; et al.
Abstract : Background: Patients with abdominal aortic aneurysm (AAA) are at significant risk of cardiovascular (CV) events. Recent implementation of AAA-screening means thousands of patients are now diagnosed with small-AAA; however, CV risk factors are not always addressed. This study aimed at assessing and quantifying the CV characteristics of patients with small AAA following the introduction of screening programmes. Methods: CV profiles of 384 men with a small AAA (<55 mm diameter) were assessed through the United Kingdom Aneurysm Growth Study (UKAGS), a nationwide prospective cohort study of men with small AAA. A prospective local cohort of an additional 142 patients with small AAA with available blood pressure (BP) and lipid profiles was also included and followed-up for 1 year. Results: In the UKAGS population, 54% were current and 30% ex-smokers; 58% were hypertensive and 54% hypercholesterolaemic. In the local group, 54% were current and 40% were ex-smokers, and 94% were hypertensive. Patients were not more likely to receive CV medication after entering AAA surveillance in either group. All local patients were clustered "high-risk" for future CV events based on the Framingham score (mean 21.8%, 95% CI 20.0–23.6), JBS-2 (16.3%, 14.7–17.9) and ASSIGN (25.2%, 22.7–27.7). No change was seen in systolic BP levels between baseline and 1 year (140.9 mmHg vs. 142.5 mmHg, p =.435). A rise was seen in cholesterol (4.0 mmol–4.2 mmol, p <.0001) values at 1 year. Conclusions: This study suggests that patients with small AAA are at significant risk for developing CV events and this is not currently addressed, which is evident by the "high-risk" CV risk profiles of these patients despite being in AAA surveillance. Design and implementation of a CV risk reduction programme tailored for this population is necessary.